The Role of the Sharia Supervisory Board in Ensuring Contract Compliance in Sharia Financial Institutions' Financing Practices - Endang Sriani; Iffatul Habibah (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2023)
Murabahah financing, in concept and principle, is intended for a sale and purchase agreement with an agreed-upon cost price and desired profit margin. However, variations exist in practice, where clients use this financing to settle their debts rather than to acquire the objects specified in the contract. Therefore, this research aims to analyze the role of the Sharia Supervisory Board (DPS) in Sharia Financial Institutions concerning Murabahah financing. This study is a field research with an empirical juridical approach. Data were gathered through interviews, observations, and document analysis, and the collected data were analyzed using a qualitative descriptive method. The results indicate that the supervision by the DPS is not optimal as it is limited to central offices and relies on information provided by management, thus not detecting violations in the field. The suggestion from this research is that the supervision would be more comprehensive if the DPS also verifies with clients as a comparative data source to ensure the conformity of products with Sharia principles.